The Impact of Knowledge Sharing on Innovative Work Behavior at PT Sumatera Hakarindo Deli Serdang - Felix Leonardi; Sri Aprianti Tarigan; Albert Tannadi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2023)
Human resource management plays a major role in the effectiveness of any organization. Employee innovativeness is engagement in innovative behaviors which includes behaviors related to the innovation process. The organizational innovation needs the knowledge sharing in the company. Knowledge sharing is considered an important process in an organization. Knowledge sharing plays an important role in creating innovation. The purpose of this research is to know whether there is the impact of knowledge sharing on innovative work behavior at PT Sumatera Hakarindo Deli Serdang. Research design used in this research is descriptive research design and correlational research design. Research methods which used are descriptive statistic analysis, validity and reliability test, normality test, coefficient correlation, coefficient of determinant, simple linear regression analysis and Z testing. The conclusion of this research is that knowledge sharing has significant impact on innovative work behavior at PT Sumatera Hakarindo Deli Serdang. Z test give result that Zcount (9.42) is higher than Ztable (1.96). Correlation value in 0.883 shows that there is strong positive relationship between knowledge sharing and innovative work behavior in PT Sumatera Hakarindo Deli Serdang. Coefficient of determination value in amount of 77.9% shows that the knowledge sharing has contribution on change of innovative work behavior in amount 77.9% while the remaining in 22.1% is contributed by other factor. The linear regression equation is Y = 2.798 + 1.497 X. Coefficient of regression in 2.798 shows that increasing of 1 unit knowledge sharing can make increasing of innovative work behavior in 2.798 unit. From respondent’s answer, it can be known that most of respondent is disagree about knowledge sharing and innovative work behavior dimension in PT Sumatera Hakarindo Deli Serdang. The company can increase the innovative work behavior with improving knowledge sharing.